Gestures in Music (Training and Practice : Journal of Educational Sciences, 2012)
Music can be classified according to several points of view: with or without text, vocal or instrumental, programme music or absolute music … and it may be considered in many other ways although any definition is much less than what music can give to the recipient. A not very well-known point of view is finding gestures in kindergarten and school songs, pieces for listening and, generally, papular compositions. Theoretical introduction is illustrated with some examples from Gregorian chant. folk music and classical music.“Expression of meaning takes place namely by words in seven per cent only while quality and components of voice, stress, intonation, melody determine meaning of message in 38 per cent and non-verbal information as mimicking, gestures and posture in 55 per cent.” (Bagdy, Pap, 2011)